TREM2 improves neurological dysfunction and attenuates neuroinflammation, TLR signaling and neuronal apoptosis in the acute phase of intracerebral hemorrhage - Liu, Sidan; Cao, Xuezhao; Wu, Zhe; Deng, Shumin; Fu, Hefei; Wang, Yanzhe; Liu, Fang (Frontiers in Aging Neuroscience, 2022)
Neuroinflammation contributes to secondary brain injury following intracerebral hemorrhage (ICH). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effect by suppressing neuroinflammatory response in experimental ischemic stroke. This study aimed to clarify the neuroprotective role of TREM2 and potential underlying mechanism in a mouse model of ICH and in vitro. Adeno-associated virus (AAV) and green fluorescent protein-lentivirus (GFP-LV) strategies were employed to enhance TREM2 expression in the C57/BL6 mice and BV2 cells, respectively. The adult male C57/BL6 mice were subjected to ICH by administration of collagenase-IV in 1 month after the AAV particles injection. An in vitro ICH model was performed with oxygen hemoglobin in BV2 cells. Toll-like receptor 4 (TLR4) antagonist TAK242 was applied at 6 h following ICH. Neurological function, TREM2, pro-inflammatory cytokines, brain water content and Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining were evaluated at 24 h following ICH. TLR4, NF-κB and mitogen-activated protein kinases (MAPK) signaling pathways were also determined by Western blot analysis at the same time point. The levels of TREM2 were increased at 12 h, peaked at 24 h and recovered on 7d following ICH. TREM2 overexpression ameliorated ICH induced neurological dysfunction, inhibited neuroinflammation, and attenuated apoptosis and brain edema. Further mechanistic study revealed that TREM2 overexpression inhibited TLR4 activation and NF-κB and MAPK signaling pathways. ICH increased the percentage of TUNEL-positive cells, which was markedly decreased by TREM2 overexpression. A similar improvement was also observed by the administration of TAK242 following ICH. TREM2 improves neurological dysfunction and attenuates neuroinflammation and neuronal apoptosis in the acute phase of ICH, which is, at least in part, mediated by negatively regulating TLR4 signaling pathway. These findings highlight TREM2 as a potential target for early brain injury following ICH.